DIVERSIFIKASI NUGGET IKAN SEBAGAI PEMENUHAN NUTRISI ANAK NELAYAN DI PANGKALAN PENDARATAN IKAN PAOTERE MAKASSAR - Farhanah Wahyu; Nur Insana; Fitri Indah Yani (Universitas Mataram, 2022)
Paotere is one of the fishery bases in Makassar City which is used by the community for the production, marketing, and processing of marine products and the development of fishing communities. Based on this, the two partner groups “Tenggiri and Milkfish” need to develop fish production. Through the provision of fish nuggets, it is expected to increase children's interest in consuming fish which are known to contain protein and omega 3 which are good for body and brain growth. Therefore, through this PKM program, the proposing team aims to: 1) increase interest in fish consumption and motivation to develop entrepreneurship in partner groups; 2) improve knowledge and skills in processing fish nuggets. Based on these objectives, there are several methods used, among others; 1) Identification of potential internal and external environment; 2) Work plan which includes preparation and implementation of activities, and 3) Training which includes product processing skills. The results obtained in this service have a positive impact on the community, especially the housewife group, that processing techniques through fish diversification can be done easily. This is supported by abundant sources of fish production and the processing techniques used in the form of tools and materials generally available on a household scale. Through this partnership program, products that increase the value of fish can increase nutritional fulfillment and fish consumption in children, as well as the skills of partner groups to improve and be more creative in processing various types of fish products.